A trip to the top of the volcano with Mouse : a TOON Book - Viva, Frank (Toon into reading., 2019)
"A boy and a mouse trek to the top of a volcano, taking in soaring trees, lunar landscapes and snow capped peaks, then return to the ancient city at the bottom"--